Associations between perceptions of road safety and active travel for school children and their parents - a health needs assessment. (15th November 2019) - Lester, Louise; Howard, Rob
Active school travel has physical, mental, social and economic benefits. However, uptake is low in the UK. The aim was to understand how road safety perceptions influence school travel choices. An epidemiological review was conducted alongside a literature review to understand evidence for effective interventions to increase active travel. A survey and qualitative focus groups gathered stakeholder views. Of 1, 646 survey responses (49 schools), 47% reported actively travelling to school during winter, and 58% in summer. Pupils believed greater numbers of serious accidents occur from active school travel than police reports, particularly overestimating cycling accidents. Focus groups with 13 teachers, 48 students and 21 parents identified active travel barriers including distance, weather, attitudes, car speed, congestion, safety, and time. Active school travel promotion should include safety perception messages. Planners and developers should consider active travel infrastructure, address structural barriers, and introduce traffic calming zones near schools.